Potensi Jenis Bahan Organik Sebagai Biostimulan dalam Meningkatkan Populasi Azospirillum sp, dan Hasil Kedelai (Glycine Max. L.) pada Inceptisol Jatinangor - Pujawati Suryatmana; Silmi Rahadiana Putri; Nadia Nuraniya Kamaluddin; Mieke Rochimi Setiawati (Fakultas Pertanian Universitas Padjadjaran, 2020)
Azospirillium is a genus of non-symbiotic N fixer bacteria, known as a biological fertilizer inoculant. The quality of Azospirillum sp. inoculant often decrease when applied outside its original habitat. Therefore, it is necessary to maintain the viability and increase its effectiveness. One way that can be done is by adding organic material as additives as a source of energy for bacteria. Potential organic materials can be used as additives to stimulate the viability, activity and effectiveness of Azospirillium sp. are coconut water, molasses and bran. The organic material contained elements such as C, N and P as the source of nutrients for Azospirillium sp. which was inoculated in Soybean (Glycine max L.) plants. This experiment aimed to examine the effect of additive application on Azospirillum sp. population, root nodules, and seed weight of soybean plants (Glycine max L.) on Jatinangor Inceptisols. The experimental design used was Randomized Block Design (RBD) consisted of combination between of Azospirillum sp. and additives type, namely molasses, coconut water and bran. The results showed that the application of a mixture of bran, molasses, and coconut water attracted the population of Azospirillum sp. higher than the control treatments. Meanwhile molasses, coconut water, and additive mixtures have the potential to increase the number of root nodules and soybean pods yields. Coconut water, molasses and bran are organic materials that have the potential as additives that stimulate the activity and increase the population of Azospirillium sp. and soybean pods.